(untitled) (Indian Journal of Arid Horticulture, 2025)
This study assessed the efficacy of emamectin benzoate 5 SG (0.0025%) in managing the shoot and fruit borer of brinjal through front line demonstrations (FLDs) conducted during 2021-22, 2022-23, and 2023-24 in Kalol Taluka and Panchmahal districts of Gujarat. The study compared demonstrated practice (emamectin benzoate 5 SG @ 12.5 g a.i./ ha) with farmer’s practice (inconsistent pesticide use). Results revealed significant reduction in pest damage under the recommended practice, with shoot borer infestation decreasing from 7.25% to 8.50% and fruit borer damage reducing from 13.50% to 15.50%, compared to 17.50%-18.75% and 22.75%-23.50%, respectively, under farmer’s practice. Yield increased from 235.25 q/ ha (2021-22) to 249.75 q/ ha (2023-24) in the recommended practice, significantly higher than farmer’s practice yields (170.50 to 198.50 q/ ha). The technology gap was 45.83 q/ ha, extension gap 55.75 q/ha, and technology index 16.37%. Economic analysis showed a B:C ratio of 3.10 for the recommended practice versus 2.56 in farmer’s practice, with an additional net return of ₹ 28,400/ ha. The study confirms that emamectin benzoate 5 SG effectively manages brinjal fruit and shoot borer, enhancing productivity and profitability, making it a viable pest control strategy for sustainable brinjal cultivation.